Integrated Volume Card Game Make A Match Learning Model: Improving Motivation of Learning Outcomes of the Concept of Spatial Building - Anggun Tri Wahyuni; Yuli Witanto (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to design, develop, and evaluate the effectiveness of an innovative interactive learning medium, a volume card game integrated with the Make a Match cooperative learning model, to enhance students' conceptual understanding of volume in mathematics. Methodology: Using an ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection tools included pretest-posttest questionnaires, expert validation sheets, and N-Gain analysis to assess the media’s validity and learning effectiveness. Statistical analysis, including the Paired Samples T-Test, was conducted using SPSS software. Main Findings: The findings revealed that the volume card game achieved a high validity score of 91% according to expert evaluations, indicating that it is well-suited for classroom use. Furthermore, the game significantly improved student learning outcomes, as evidenced by the Paired Samples T-Test results (p = 0.000) and an N-Gain score of 0.7575, which falls in the high category. Positive feedback was overwhelming, with 98.6% of students reporting that the game was engaging, enjoyable, and effective in fostering their understanding of volume concepts. Novelty/Originality of this study: This study introduces an innovative combination of interactive learning tools and cooperative learning strategies, addressing the challenges of teaching abstract mathematical concepts. By merging gamification with collaborative learning, the volume card game provides an engaging and practical approach to enhance motivation and deepen conceptual understanding. The novelty of this research lies in its dual focus on integrating educational games with cooperative learning and demonstrating its scalable potential for application in broader mathematical topics and academic contexts.